Friction reduction mechanisms in multilayer graphene sliding against hydrogenated diamond-like carbon. (November 2016) - Bhowmick, S.; Banerji, A.; Alpas, A.T.
Abstract: By examining sliding-induced damage and interfacial material transfer processes that occur when multilayer graphene (MLG) is placed in contact with diamond-like carbon (DLC) and N- based coatings as well as uncoated steel the role of counterface materials on the friction of MLG has been elucidated. Sliding friction tests conducted on MLG in an ambient testing environment (45% RH) and under the same loading conditions showed that tribo-chemical mechanisms would differ depending on the counterface material. While the N-based coatings, e.g., TiCN counterface, inflicted the most extensive sliding wear damage to MLG resulting in a high coefficient of friction (COF), lesser damage occurred against 52100 steel counterface accompanied by the formation of graphene transfer layers on the counterface which was a necessary condition for low friction in tribosystems not involving carbonaceous counterfaces. A common feature of the worn MLG was the sliding induced defects which comprised of edge fracture, fragmented/bent graphene stacks compared to pristine graphene and disordered regions between them. When MLG was run against a C-based counterface, namely hydrogenated (40% H) diamond like carbon (H-DLC) coating a low COF of 0.08 resulted without formation of detectable transfer layers. Sliding induced defect activated H2 O dissociation and adsorption of H and OH at the defect sites were likely to be responsible for the low friction of MLG sliding against H-DLC.